COMMUNITY SERVICE EDUCATION OF ELDERLY NUTRITION BASED ON LOCAL CULTURE FOOD TO REALIZE RESILIENT AND INDEPENDENT ELDERLY IN MEDAN TUNTUNGAN DISTRICT - Reny Juliana Sihombing; Nurliaty; Sestika Matondang (Jurnal Masyarakat Indonesia (Jumas), 2024)
Entering old age (elderly), the body experiences various physiological changes that have an impact on nutritional status and a decrease in self-care. This community service activity aims to improve the knowledge and skills of the elderly in managing daily nutrition independently by utilizing the potential of local cultural food. The activity was carried out in Medan Tuntungan District by the academic team from STIKes Darmo Medan, involving 2 lecturers and 1 student with the main target of the elderly and their families. The intervention methods used are direct health counseling and education on nutrition management based on local wisdom. Program evaluation is carried out through psychomotor assessment and comparison of pre-test and post-test results to measure the improvement of participants' knowledge. The results of the activity showed that there was an increase in the awareness of the elderly and families in compiling a balanced nutritional composition and eliminating negative perceptions of healthy food. In conclusion, nutrition self-care education based on local cultural food is effective as an applicative strategy to realize the elderly who are resilient, independent, and improve their quality of life in a sustainable manner.